Recent Advances in Chlorination: Novel Reagents and Methods from the Last Decade - Vogel, Iago C.; Pinto, Diana C. G. A.; Candeias, Nuno R. (SynOpen, 2024)
Chlorinated compounds are vital in organic synthesis, impacting nucleophilic substitutions, β-elimination, and C–H acidity. Herein, recent advances in (hetero)arene chlorination, focusing on novel reagents and methods developed in the past decade, are showcased. Traditional electrophilic agents such as Cl2 and PCl5 have been expanded with new chlorinating agents such as Palau’chlor, as well as with electrochemical and photochemical techniques. Biocatalyzed chlorination using FAD-dependent halogenases has also been explored. Key trends include green chemistry with eco-friendly chlorine sources like NaCl and HCl. Although nucleophilic chlorination remains rare, electrochemical methods show promise, despite equipment limitations. This graphical review highlights significant progress in the last decade towards more sustainable and efficient chlorination strategies.
Keywords: (hetero)arene chlorination; electrophilic substitution; nucleophilic chlorination; chlorinating agents; electrochemistry; photocatalysis; biocatalysis; green chemistry